Solvent-controlled quadruple catenation of giant chiral (8+12) salicylimine cubes driven by weak hydrogen bonding - Wagner, Philippe; Rominger, Frank; Gross, Jürgen H.; Mastalerz, Michael (Angewandte Chemie. International edition, 2023)
Mechanically interlocked structures are fascinating synthetic targets and the topological complexity achieved through catenation offers numerous possibilities for the construction of new molecules with exciting properties. In the structural space of catenated organic cage molecules, only few examples have been realized so far, and control over the catenation process in solution is still barely achieved. Herein, we describe the formation of a quadruply interlocked catenane of giant chiral [8+12] salicylimine cubes. The formation could be controlled by the choice of solvent used in the reaction. The interlocked structure was unambiguously characterized by single crystal X-ray diffraction and weak hydrogen bonding was identified as a central driving force for the catenation. Furthermore, scrambling experiments using partially deuterated cages were performed, revealing that the catenane formation occurs through mechanical interlocking of preformed single cages.
Im Titel steht der Ausdruck (8+12) in eckiger Klammer
Online veröffentlicht: 25. Januar 2023
Gesehen am 24.08.2023